Method design of interactive digital devices to support the workspace comfort - Athifa Sri Ismiranti; Akhmadi Akhmadi; Arini Arumsari; Mahendra Nur Hadiansyah; Alfito Aji Denandra; Sarah Nurul Azizah (International Journal of Visual and Performing Arts, 2023)
There are many alterations and adaptations of the workspaces after the Covid-19 pandemic. Nowadays, workspaces are required to have flexibility in facilitating physical and virtual activities, work-from-home (WFH), and work-from-office (WFO) activities. Besides, workspaces must provide comfort based on user preferences and demand to support workers’ health and productivity. In order to answer these problems, the design of interactive digital devices that can be adjusted according to physical needs, activities, and preferences is needed to support the ideal workspace comfort. The research method used in this research is a literature review related to ideal workspace comfort standards and an assessment of the Arduino as an interactive digital device to produce an interactive digital device method design that can detect ideal comfort and be applied to workspaces. The result shows that as an interactive digital device, Arduino can be implemented in a workspace to detect and produce ideal workspace comfort regarding lighting, noise, temperature, and humidity. Arduino also supports flexibility and varied demand in a workspace because of its adjustable artificial intelligence feature. The ideal standard of workspace differs based on the activities and geographical conditions of the country and is related to the varied preferences of its users. Based on its complexity, for further research to be carried out, it is recommended to conduct a case study of ideal workspace interior design with an Arduino device in a specific place to generate more accurate data and suitable workspace design.